2018
DOI: 10.2118/183933-pa
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant/Polymer Flooding: Chemical-Formulation Design and Evaluation for Raudhatain Lower Burgan Reservoir, Kuwait

Abstract: Summary Surfactant/polymer (SP) flooding is an enhanced-oil-recovery (EOR) process that can lead to incremental oil recovery through two mechanisms: reducing oil/water interfacial tension (IFT) to decrease residual oil saturation and increasing the viscosity of the displacing fluid to improve overall sweep efficiency. IFT reduction allows better oil recovery by overcoming capillary effects, while the increased viscosity of the displacing fluid allows a more-homogeneous sweep of reservoir oil. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…As our economic analysis showed even small projects can be very profitable. Examples of pilot studies (Windalia and Matzan fields) can be used as templates for the pilot design and pilot simulation applications (Al-Murayri et al 2018, Haynes et al 2013, Lüftenegger et al 2016). Based on the information from the field pilots and economic models, deployment plans are more likely to be executed if they are driven by the economic aspects.…”
Section: Discussionmentioning
confidence: 99%
“…As our economic analysis showed even small projects can be very profitable. Examples of pilot studies (Windalia and Matzan fields) can be used as templates for the pilot design and pilot simulation applications (Al-Murayri et al 2018, Haynes et al 2013, Lüftenegger et al 2016). Based on the information from the field pilots and economic models, deployment plans are more likely to be executed if they are driven by the economic aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the Winsor-based graphs was used as suggested for surfactantbased formulation development presented by (Al-Murayri et. al.2019a, Al-Murayri et al 2018a. Figure 2 shows an example of them.…”
Section: Phase Behaviour and Formulation Designmentioning
confidence: 99%
“…In the previous section, we discussed the importance of the Winsor sensitivity graph for the evaluation of the surfactant formulation. We suggest an extended version of the Winsor graph reported by Al-Murayri et al 2018a where aqueous solubility map and static adsorption can be reported.…”
Section: Surfactant Formulation Sensitivity Graphsmentioning
confidence: 99%
“…hệ số thu hồi tăng thêm 15% so với tổng trữ lượng dầu tại chỗ (original oil in place -OOIP). Đến nay, có nhiều mỏ trên thế giới áp dụng thành công bơm ép ASP (alkaline surfactant polymer) để nâng cao hệ số thu hồi dầu từ 15 -33% như ở mỏ Raudhatain [6], mỏ dầu nặng tại vịnh Bohai [7] , mỏ Algyő [8]… Mục tiêu quan trọng khi nghiên cứu, đánh giá khả năng ứng dụng giải pháp nâng cao hệ số thu hồi dầu là tính toán, xác định được hiệu quả kỹ thuật của giải pháp khi xem xét triển khai trên phạm vi toàn mỏ. Để đạt được mục tiêu này, ứng dụng mô hình mô phỏng khai thác mỏ là công cụ tối ưu nhất hiện nay.…”
Section: Tóm Tắtunclassified